Cambridge IGCSE business studies : coursebook - "Fisher, Mark" (Cambridge University Press London, 2014)
This revised set of resources for Cambridge IGCSE Business Studies syllabus 0450 (and Cambridge O Level Business Studies syllabus 7115) is thoroughly updated for the latest syllabus for first examinations from 2015.